2015
DOI: 10.1002/hed.23974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human thyroid‐stimulating hormone or levothyroxine withdrawal on salivary gland dysfunction after radioactive iodine administration for thyroid remnant ablation

Abstract: The use of rhTSH for preparation of radioactive iodine ablation as opposed to LT4 withdrawal reduces the incidence of salivary gland dysfunction. © 2015 Wiley Periodicals, Inc. Head Neck 38: E227-E230, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In addition, Hoffman et al propose being more conservative with RAI or avoiding it when feasible in cases of low risk thyroid cancer to counteract the dose-dependent risk of sialadenitis [ 17 ]. Another study conducted by Iakovou et al showed that the use of thyrogen for preparation of RAI ablation as opposed to LT4 withdrawal reduces the prevalence of salivary gland dysfunction, possibly due to reduced hypothyroidism [ 18 ]. In our study, we could not replicate the abovementioned factors, mainly because very few subjects received thyrogen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hoffman et al propose being more conservative with RAI or avoiding it when feasible in cases of low risk thyroid cancer to counteract the dose-dependent risk of sialadenitis [ 17 ]. Another study conducted by Iakovou et al showed that the use of thyrogen for preparation of RAI ablation as opposed to LT4 withdrawal reduces the prevalence of salivary gland dysfunction, possibly due to reduced hypothyroidism [ 18 ]. In our study, we could not replicate the abovementioned factors, mainly because very few subjects received thyrogen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these consequences, the conventional method has other drawbacks such as the long preparatory period (two weeks or longer) for diagnosis, persistent symptoms from hypothyroidism even after examination, and the risk of carcinoma cell growth. In contrast, the use of rhTSH has several advantages in terms of maintaining the QoL, shortening of the preparatory periods for diagnosis, avoiding hypothyroidism, having less chance of damage to the salivary gland [206], minimizing the stimulation of cancer cell growth [207,208], and alleviating radiation exposure by maintaining the renal function [209,210]. Adverse events associated with the use of rhTSH include headache, nausea, vomiting, general fatigue, and dizziness, although they are rare.…”
Section: Adverse Events Associated With Therapiesmentioning
confidence: 99%
“…The severity of post-RAI xerostomia in DTC patients was assessed by the Xerostomia Inventory score (XI Score), the applicability of which has been validated in other studies (19,21). The English version of the XI Score was translated into a Chinese version for participants to conduct the questionnaire.…”
Section: Xerostomia Inventory Scorementioning
confidence: 99%
“…The XI Score's 11 options have a total score between 11 and 55 points. According to the size of the participants' XI total score, the participants were divided into three grades (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) points: no to mild xerostomia; 24-39 points: moderate to severe xerostomia; 40-55 points: severe to extreme xerostomia).…”
Section: Xerostomia Inventory Scorementioning
confidence: 99%